Brain MRI: a useful tool for screening of hypertensive patients for silent cerebro-vascular damage - Rana, Meena K.; Thakur, Manish K.; Gupta, Dhruv (International Journal of Research in Medical Sciences, 2018)
Background: Worldwide hypertension is an important public-health challenge because of its high frequency and concomitant risks of cardiovascular, renal, cerebrovascular disease and death. Current guidelines for the management of hypertension mainly recommend the search for preclinical damage to the heart and kidneys. However, extending this search to other organs, for instance the brain, might improve risk stratification, might optimize antihypertensive therapy and might, in the end help to further reduce the burden of disease attributable to hypertension. Methods: 84 consecutive hypertensive patients with no target organ damage were enrolled in study to find out silent brain damage over a period of one year. Results: Mean body mass index (BMI) of the study population was 28.4±2.5 kg/m2 (range 23.2 to 35.3kg/m2). 33 (39.3%) subjects had white matter lesions. 13 (15.47%) study subjects were found to have vascular changes which included micro angiopathic changes, infarcts and reduced/slow blood flow. 33 (39.3%) subjects were found to have normal brain MRI in the study. Early brain MRI was found to be beneficial in patients who had uncontrolled blood pressure either due to lack of treatment or irregular use of anti-hypertensive treatment. This was true for every age group in general and particularly in subjects above the age of 50 years. Conclusions: The screening of hypertensive patients for silent cerebrovascular damage with brain MRI may be useful in stratifying the risk of future cerebrovascular disease.